Better lung protection following death due to rapid exsanguination in rats - LAÇİN, BERNA; ERCAN, FERİHA; BATIREL, HASAN FEVZİ; BOSTANCI, KORKUT; YÜKSEL, MERAL (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2012)
Background: This study aims to investigate the effects of death due to rapid exsanguination on the viability of lung tissue. Methods: Fourty-six Sprague-Dawley male rats with a weight range of 310-370 g were included in the study. Rats were divided into six groups: (i) ischemic alone (I group; n=8); (ii) passive exsanguination group of whose major abdominal veins were cut following death (PE group; n=8) (iii) group of whose major abdominal veins were cut and sacrified with rapid exsanguination (RE group; n=8); (iv) lung perfusion group with saline (SP group; n=8); (v) lung perfusion group with Perfadex (PP group; n=8) and (vi) control group (C group; n=6). Rats in all experiement groups except rapid exsanguination ones and all in the control group were euthanized with intrahepatic pentobarbital. Lungs were removed following euthanasia in the controls. In all study groups, lungs were ventilated in the cadavers at room temperature for 120 minutes and kept in warm ischemia. Results: Myeloperoxidase (MPO) activity, luminol chemiluminescence (CL) values and non-viable cell rate were higher in the ischemia group. The PE group had increased MPO activity, lucigenin CL values and nonviable cell rate, whereas the RE group had reduced MPO activity and luminol CL values, compared to ischemia group. MPO activity, lucigenin CL levels and non-viable cell rate were lower in the RE group, compared to PE. The PP had lower MPO activity and luminol CL values, compared to SP or ischemia group, whereas non-viable cell rate increased. Conclusion: Death following rapid exsanguination results in better preservation of lung viability and minimal oxidative injury. This may be explained by rapid loss of platelets and inflammatory cells in the tissue and shift of extravascular fluid to intravascular compartment.
Keywords: Cadaveric lung; donor lung; ischemic injury; lung transplantation; organ preservation; HEART-BEATING DONOR; ISCHEMIA-REPERFUSION INJURY; OFFICIAL ADULT LUNG; INTERNATIONAL-SOCIETY; PULMONARY VIABILITY; REACTIVE OXYGEN; WARM ISCHEMIA; FREE-RADICALS; MYELOPEROXIDASE; DIE